Comutation and exclusion analysis in human tumors: A tool for cancer biology studies and for rational selection of multitargeted therapeutic approaches. Issue 4 (25th January 2019) - Ochoa, Soledad; Martínez‐Pérez, Elizabeth; Zea, Diego Javier; Molina‐Vila, Miguel Angel; Marino‐Buslje, Cristina
Abstract: Malignant tumors originate from somatic mutations and other genomic and epigenomic alterations, which lead to loss of control of the cellular circuitry. These alterations present patterns of co‐occurrence and mutual exclusivity that can influence prognosis and modify response to drugs, highlighting the need for multitargeted therapies. Studies in this area have generally focused in particular malignancies and considered whole genes instead of specific mutations, ignoring the fact that different alterations in the same gene can have widely different effects. Here, we present a comprehensive analysis of co‐dependencies of individual somatic mutations in the whole spectrum of human tumors. Combining multitesting with conditional and expected mutational probabilities, we have discovered rules governing the codependencies of driver and nondriver mutations. We also uncovered pairs and networks of comutations and exclusions, some of them restricted to certain cancer types and others widespread. These pairs and networks are not only of basic but also of clinical interest, and can be of help in the selection of multitargeted antitumor therapies. In this respect, recurrent driver comutations suggest combinations of drugs that might be effective in the clinical setting, while recurrent exclusions indicate combinations unlikely to be useful. Abstract : Malignant tumors somatic mutations present patterns of co‐occurrence and mutual exclusivity. These dependencies can influence prognosis and modify response to drugs, highlighting the need for multitargeted therapies. We present a comprehensive analysis of co‐dependencies of somatic mutations in human tumors uncovering pairs and networks of comutations and exclusions, some of them restricted to certain cancer types and others widespread. Comutations suggest combinations of drugs that might be effective in the clinical setting, while exclusions indicate combinations unlikely to be useful.